Is there a Connection between Inflammatory Bowel Disease Exacerbation, Clostridium difficile Infection and Thrombocytosis? - Marusic Marinko; Luetic Kresimir; Belosic-Halle Zeljka; Troskot Peric Rosana; Dominkovic Lucija; Gulic Sasa (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Aim: To show if there is any connection between the activity of inflammatory bowel disease (IBD), infection with Clostridium difficile (C. difficile) and thrombocytosis in our hospitalized patients.  Methods: We performed a retrospective observational study to determine the incidence of C. difficile infection (CDI) and thrombocytosis in our patients with IBD hospitalized from January 1, 2007- December 31, 2012. Results: A total of 363 hospitalized patients were identified during the observed 6-year period with a diagnosed IBD (258 patients with ulcerative colitis (UC) and 105 patients with Crohn's disease (CD). 28 (21.7%) patients with the exacerbation of UC and 17 (34.7%) patients with the exacerbation of CD were positive for CDI. Thrombocytosis was present in 65 (50.4%) patients with the exacerbation of UC and 39 (79.6%) patients with the exacerbation of CD. 26 (14.6%) patients with IBD exacerbation (15 patients with UC and 11 patients with CD) had both CDI and thrombocytosis. Statistically significant difference was found only in the incidence of thrombocytosis in patients with UC compared to patients with CD and all IBD patients. Conclusion: We recommend testing all hospitalized IBD patients with an exacerbation for CDI because of the high prevalence of CDI in these patients and the prognostic implications of CDI in these patients. Further studies with a larger number of patients are needed to investigate the real importance of CDI and thrombocytosis in patients with IBD exacerbation and also to show if any connection between those two parameters exists.